Peran Digitalization Intensity Dalam Memoderasi Pengaruh Financial Stability Terhadap Fraudulent Financial Statement - Juniar Prayoga, Cepi; Resmi Afifah Fadilah; Reny Dany Merliyana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
This study investigates the influence of Financial Stability  on Fraudulent Financial Statement s (FFS) and examines whether Digitalization Intensity  plays a moderating role in this relationship within the Indonesian banking industry. Although regulatory oversight and digital transformation in the banking sector continue to intensify, cases of financial reporting fraud remain a serious concern. This research adopts a quantitative explanatory design using a purposive sampling method on eight major commercial banks operating in Indonesia. The data are analyzed using Moderated Regression Analysis (MRA). The findings reveal that Financial Stability  has a negative and significant effect on FFS, indicating that banks with more stable financial conditions tend to have a lower tendency to engage in financial statement fraud. In contrast, Digitalization Intensity  does not show a significant direct effect on FFS and also fails to moderate the relationship between Financial Stability  and FFS. These results indicate that financial pressure continues to be the primary driver of fraudulent behavior, while the application of digital technology has not yet optimally functioned as an effective control mechanism. This study enriches the empirical discourse on financial reporting fraud in the banking sector and offers practical insights for regulators and bank management in strengthening technology-based supervisory systems.